(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The second era of the various Jadid societies in Turkestan, spanning from the early 20th century until the Russian Revolution of 1917, marked a significant phase of consolidation and expansion of progressive ideals among Central Asian intellectuals. Their activities included secret meetings, the publication of reformist literature, the establishment of modern schools, and political organizations aimed at awakening the masses to the possibilities of national liberation. Despite the harsh repression from colonial authorities, these societies persisted in spreading their message of social and educational change, creating the groundwork for later political movements in Central Asia.